Nickel-catalyzed highly chemo- and stereoselective borylative cyclization of 1, 6-enynes with bis(pinacolato)diboron. Issue 8 (25th May 2017) - Hsieh, Jen-Chieh; Hong, Ya-Chun; Yang, Chun-Ming; Mannathan, Subramaniyan; Cheng, Chien-Hong
Abstract : A highly chemo- and stereoselective nickel-catalyzed borylative cyclization of 1, 6-enynes with bis(pinacolato)diboron. Abstract : A highly chemo- and stereoselective nickel-catalyzed borylative cyclization of 1, 6-enynes with bis(pinacolato)diboron is described. Enynes containing an electron-deficient alkene such as a vinyl ketone provided alkenylboronates while enynes containing a terminal alkene gave homoallylic boronates. A plausible mechanism involving a nickelacyclopentene intermediate is proposed. In addition, the resulted alkenyl- or homoallylic boronates can be transformed to the corresponding ketones and alcohols via oxidation. Application to a palladium-catalyzed cross coupling reaction of alkenylboronates with aromatic halides has been demonstrated as well.